2018
DOI: 10.1515/ijcre-2017-0136
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of MgO/TiO2 Nanocomposite and Its Application in Photocatalytic Dye Degradation

Abstract: The application of nanoparticles in dye degradation is one of the trending arenas of research in the present day world. In this work, we report a novel route to synthesise MgO/TiO2 metal oxide nanocomposite by microemulsion technique and its application in photocatalytic dye degradation. Oil in water microemulsion was prepared using Span 80 and Tween 80 as surfactants whose proportion was regulated using hydrophilic and lipophilic Balance (HLB). The obtained microemulsion was then mechanically stirred and calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The calcination of microemulsion was carried out to obtain the fine doped particles, and different concentrations of synthesized catalyst (0.4, 0.6, 0.8, 1.0 and 1.2 g L −1 ) were tested for the degradation of different amounts (20,40,60,80, 100 mg L −1 ) of methyl red dye. Amongst all the combinations, 1 g L −1 of catalyst load showed a maximum degradation potential (84.8%) for 20 mg L −1 concentration of methyl red dye in 60 min which was accounted as 11.3% more than native TiO 2 NPs (Sathish Kumar et al 2018). The microemulsion method was also employed to synthesize carbon (C)-doped TiO 2 /CdS core-shell NPs (Lavand et al 2015), wherein the morphology characterization data obtained by TEM revealed that C/TiO 2 /CdS core-shell heterostructure composites with CdS as an inner core and C-doped TiO 2 as the outer shell were successfully obtained by the microemulsion method.…”
Section: Microemulsionmentioning
confidence: 99%
See 1 more Smart Citation
“…The calcination of microemulsion was carried out to obtain the fine doped particles, and different concentrations of synthesized catalyst (0.4, 0.6, 0.8, 1.0 and 1.2 g L −1 ) were tested for the degradation of different amounts (20,40,60,80, 100 mg L −1 ) of methyl red dye. Amongst all the combinations, 1 g L −1 of catalyst load showed a maximum degradation potential (84.8%) for 20 mg L −1 concentration of methyl red dye in 60 min which was accounted as 11.3% more than native TiO 2 NPs (Sathish Kumar et al 2018). The microemulsion method was also employed to synthesize carbon (C)-doped TiO 2 /CdS core-shell NPs (Lavand et al 2015), wherein the morphology characterization data obtained by TEM revealed that C/TiO 2 /CdS core-shell heterostructure composites with CdS as an inner core and C-doped TiO 2 as the outer shell were successfully obtained by the microemulsion method.…”
Section: Microemulsionmentioning
confidence: 99%
“…Microemulsion is an innovative technique, used to fabricate extremely minute particles, which allows controlling the size when synthesizing nanocomposites and prevents the accumulation of these NPs. Sathish Kumar et al (2018) used the microemulsion method for the synthesis of MgO-doped titanium oxide NPs, and these composites were evaluated for their photocatalytic dye degradation efficiency under UV-visible light illumination. Span 80 and Tween 80 were utilized to produce oil in water microemulsion, and their percentage was balanced by hydrophilic and hydrophobic equilibrium, followed by mechanical agitation.…”
Section: Microemulsionmentioning
confidence: 99%